The labour of leisure : the culture of free time - Rojek, Chris (Sage Publications, 2010)
Leisure has always been associated with freedom, choice and flexibility. The week-end and vacations were celebrated as 'time off'. In his compelling new book, Chris Rojek turns this shibboleth on its head to demonstrate how leisure has become a form of labour. Modern men and women are required to be competent, relevant and credible, not only in the work place but with their mates, children, parents and communities. The requisite empathy for others, socially acceptable values and correct forms of self-presentation demand work. Much of this work is concentrated in non-work activity, compromising.